Altered Epigenetic Marks and Gene Expression in Fetal Brain, and Postnatal Behavioural Disorders, Following Prenatal Exposure of Ogg1 Knockout Mice to Saline or Ethanol - Shama Bhatia; David Bodenstein; Ashley P. Cheng; Peter G. Wells (Cells, 2023)
Oxoguanine glycosylase 1 (OGG1) is widely known to repair the reactive oxygen species (ROS)-initiated DNA lesion 8-oxoguanine (8-oxoG), and more recently was shown to act as an epigenetic modifier. We have previously shown that saline-exposed Ogg1 −/− knockout progeny exhibited learning and memory deficits, which were enhanced by in utero exposure to a single low dose of ethanol (EtOH) in both Ogg1 +/+ and −/− progeny, but more so in Ogg1 −/− progeny. Herein, OGG1-deficient progeny exposed in utero to a single low dose of EtOH or its saline vehicle exhibited OGG1- and/or EtOH-dependent alterations in global histone methylation and acetylation, DNA methylation and gene expression (Tet1 (Tet Methylcytosine Dioxygenase 1), Nlgn3 (Neuroligin 3), Hdac2 (Histone Deacetylase 2), Reln (Reelin) and Esr1 (Estrogen Receptor 1)) in fetal brains, and behavioural changes in open field activity, social interaction and ultrasonic vocalization, but not prepulse inhibition. OGG1- and EtOH-dependent changes in Esr1 and Esr2 mRNA and protein levels were sex-dependent, as was the association of Esr1 gene expression with gene activation mark histone H3 lysine 4 trimethylation (H3K4me3) and gene repression mark histone H3 lysine 27 trimethylation (H3K27me3) measured via ChIP-qPCR. The OGG1-dependent changes in global epigenetic marks and gene/protein expression in fetal brains, and postnatal behavioural changes, observed in both saline- and EtOH-exposed progeny, suggest the involvement of epigenetic mechanisms in developmental disorders mediated by 8-oxoG and/or OGG1. Epigenetic effects of OGG1 may be involved in ESR1-mediated gene regulation, which may be altered by physiological and EtOH-enhanced levels of ROS formation, possibly contributing to sex-dependent developmental disorders observed in Ogg1 knockout mice. The OGG1- and EtOH-dependent associations provide a basis for more comprehensive mechanistic studies to determine the causal involvement of oxidative DNA damage and epigenetic changes in ROS-mediated neurodevelopmental disorders.